Peranan Keteladanan Dan Kecerdasan Interpersonal Seorang Guru Terhadap Karakter Siswa Di SD IT Ulul Albab - Rahmadani Fitri, Umar Darwis (Journal of Educational Research and Humaniora (JERH), 2023)
The teacher's example is very influential on the character of students because it will support their personal development as well as intelligence. Teachers who have good intelligence will give birth to students who are intelligent according to their nature. God bestows every human being with different intelligence. Intelligence referred to here is interpersonal intelligence. Interpersonal intelligence includes empathy, caring, sensitivity, good at communicating verbally/non-verbally. With this ability the teacher's role greatly influences students in their social interactions and increasingly their communication. The example of a teacher and the teacher's interpersonal intelligence influence the way students communicate and adapt to social interactions in society. If the teacher succeeds in being a good example then students will show the same attitude and vice versa if the teacher behaves badly then students will behave the same. Set good examples such as discipline, caring, attention, authority, empathy, and mutual respect. Honest, patient, fair, and speaking are qualities that must be exemplified and become a habit for teachers to their students. The problem in this study is how the role of role model and interpersonal intelligence of the teacher has on the character of students at the Ulul Albab Elementary School. The purpose of this study is to find out the answers to the problems above. Therefore, this study uses a qualitative approach by taking data sources from interviews, questionnaires, observation, and documentation. Data analysis techniques were obtained from data reduction, data presentation, and data verification. The informants in this study were class teachers, study teachers and upper class students. The results of the study found that the role of exemplary and interpersonal intelligence of teachers was partly good. but still needs coaching for some teachers who don't play a role in setting an example. There are some teachers who lack discipline, lack of attention to students, inappropriate communication, lack of teacher performance and others. Likewise, the character of some students is already good but there are still some students who are still not good in character. Habituation and exemplary methods and social customs such as communication ethics, how to speak to younger or younger people have not been implemented optimally.